STUDY ON OCEANGRAFHIC AND WEATHER CONDITIONS RELATED TO THE ABUNDANCE OF SMALL PELAGIC FISHERY IN NATUNA SEA USING REMOTE SENSING DATA - Prayogo, Teguh; Arthana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 1, 2012)
Indonesian waters have abundance of natural resources; the potential of small pelagic fish in Natuna Sea and South China Sea have not been optimized yet explores. Unfortunately, it was caused by lacking in the data of environmental conditions that have been changed and the information of appropriate fishing ground. Hence, dynamical oceanographic information and weather condition is necessary to optimize small pelagic fish exploitation. Research location in Natuna Sea and its surrounding with geographical position is 08°N–03°S; 103°–111°E. The oceanographic condition representative by monthly SST, Chl-a, SSH that derived from satellite data and Dipole Mode Index for 2002-2007 from FRCGC website. Monthly wind data is variable for weather condition. Small pelagic fish abundance representative by annual fish production (2002-2005) and monthly Catch Per Unit Effort (CPUE) of Goldstripe sardinella, Bigeye scad and Indian scad (2006). It was data collected from Directorate General of Capture Fisheries (Ministry of Marine Affairs and Fisheries) and daily fishing operation (2007) used to calculate match-up ratio that was collected from Pemangkat fishing port in West Kalimantan. Research process consists of image processing, descriptive correlation analysis and GIS analysis to predict fishing ground map and match-up ratio calculation. Result of this research is the annual fish catch production of Bigeye scad and Indian scad (2002-2005) is tend to increase and the monthly CPUE of both species is high during SE Monsoon (May-Sep) that is condition contrarily in NW Monsoon (Nov-Apr). Meanwhile, the annual fish catch production of Goldstripe sardinella production is tend to decrease from 2002-2005, it has CPUE is high in early SE Monsoon (May). During the SE Monsoon (May-Sep) when DM Index is positive (+) the Indian scad and Bigeye scad production is high, for Goldstripe sardinella the fish production is high when DM Index is positive (+) in May. The accuracy of prediction map of small pelagic fishing ground in Natuna Sea is about 0.61, 0.76 and 0.81 for Goldstripe sardinella, Indian scad and Bigeye scad, respectively.
Keywords: oceanographic condition, weather condition, small pelagic fish, satellite data